New cutoff point of Prostate-Specific Antigen (PSA) and PSA Density (PSAD) to enhance diagnostic specificity for prostate cancer (Pca) in country with low prostate cancer incidence (Medical Journal of Indonesia, 2000)
[no abstract available]